Pengaruh Harga, Kualitas Produk, Dan Citra Merek Terhadap Keputusan Pembelian Mie Sedap Instant (Studi Kasus Pada Ibu – Ibu Rumah Tangga Di Desa Sei Lama Kec. Simpang Empat Kab. Asahan) - Fitriana Siahaan; Aris Siregar; M. Umar Maya Putra (JURNAL REGIONOMIC, 2018)
This study aims to determine and analyze the influence of Price, Product Quality,and Brand Image of Decision Purchase Instant Noodles. This study uses 88 respondents assample research and technique of determining the sample using purposive samplingmethod.Data analysis method used is descriptive analysis method and multiple linierregression analysis method. The data used are primary data and secondary data obtainedthrough documentation studies, interviews and questionnaires whose measurements usedifferential semantic scales. Hypothesis testing by using multiple linear regressionanalysis.The results showed that simultaneously the price, Product Quality, and BrandImage significantly influence the Decision Purchase Instant Noodle. Partially, price hasno significant effect, while brand image has significant effect. Brand image is the dominant factor influencing the Decision of Buying Instant Noodle. The value of Adjusted R Squareis 0,222, meaning 22,2% Purchasing Decision of Instant Instant Noodle can be explainedby Price, Product Quality, And Brand Image, and the rest 77,8% explained by factors notexamined in this research.